2022
DOI: 10.14309/ajg.0000000000001781
|View full text |Cite
|
Sign up to set email alerts
|

Pickle Juice Intervention for Cirrhotic Cramps Reduction: The PICCLES Randomized Controlled Trial

Abstract: Overall, 74 patients completed the trial, aged 56.6 6 11.5 years, 54% male, 41% with ascites, 38% with encephalopathy, and model for end-stage liver disease-sodium score 11.2 6 4.9. Many patients were receiving other cramp therapies at baseline. The baseline VAS for cramps was 4.2 6 3.4, the EQ-5D was 0.80 6 0.10, and 43% rated sleep as poor. At trial completion, the respective values for the pickle juice and control arms were 22.25 6 3.61 points on the VAS for cramps, compared with control tap water (20.36 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Cirrhosis is associated with multiple common physical and psychological symptoms that can be improved with treatment (Table 2). In an RCT of 80 patients, compared with tap water, 1 sip of pickle brine at cramp onset significantly reduced cramp severity at 28-day follow-up (2.3- vs 0.4-point reduction on a 10-point visual analog scale) . In a 2-week randomized, double-blind, crossover trial of 30 patients, compared with placebo, 1000 mg of taurine twice daily significantly reduced leg cramping (7 fewer cramps compared with placebo) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cirrhosis is associated with multiple common physical and psychological symptoms that can be improved with treatment (Table 2). In an RCT of 80 patients, compared with tap water, 1 sip of pickle brine at cramp onset significantly reduced cramp severity at 28-day follow-up (2.3- vs 0.4-point reduction on a 10-point visual analog scale) . In a 2-week randomized, double-blind, crossover trial of 30 patients, compared with placebo, 1000 mg of taurine twice daily significantly reduced leg cramping (7 fewer cramps compared with placebo) .…”
Section: Discussionmentioning
confidence: 99%
“…Pickle juice: reduction of 2.3 points on VAS for cramp severity compared with 0.4 for a tap-water control among 80 patients in a randomized trial…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, in June of 2022, we published the PICCLES trial of pickle juice for cramps in cirrhotics. This study concluded that sips of pickle juice at onset of cramps improve cramp severity without adverse events (2). This clinically relevant and readily available home remedy can improve the quality of life for our patients.…”
Section: What Has Ajg Done To Enhance the Reader's Experience?mentioning
confidence: 96%
“…Our interventional studies are of the highest quality, including a number of randomized controlled trials (RCTs). Many patients with liver disease struggle with uncontrolled cramping, in this issue Tapper et al provide data from a RCT of pickle juice for reduction of cramps (PICCLES) (2). Read on for data on this simple, sweet and salty way to improve our patients' symptoms.…”
mentioning
confidence: 99%